2006
DOI: 10.1021/ef050434l
|View full text |Cite
|
Sign up to set email alerts
|

Methane/CO2 Sorption Modeling for Coalbed Methane Production and CO2 Sequestration

Abstract: A thorough study of the sorption behavior of coals to methane and carbon dioxide (CO 2 ) is critical for carbon sequestration in coal seams and enhanced coalbed methane recovery. This paper discusses the results of an ad/de-sorption study of methane and CO 2 , in single gas environment, on a set of coal samples taken from the San Juan and Illinois Basins. The results indicate that, under similar temperature and pressure conditions, coals exhibit higher affinity to CO 2 as compared to methane and that the prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
143
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 242 publications
(154 citation statements)
references
References 37 publications
10
143
0
1
Order By: Relevance
“…The value of P L can also be a measure of the isotherm curvature: the smaller the value of P L , the greater the initial slope of the isotherm [43]. A least-squares fit of methane adsorption isotherms based on the Langmuir model was applied to determine the Langmuir parameters, including V L and P L .…”
Section: Pore Characteristicsmentioning
confidence: 99%
“…The value of P L can also be a measure of the isotherm curvature: the smaller the value of P L , the greater the initial slope of the isotherm [43]. A least-squares fit of methane adsorption isotherms based on the Langmuir model was applied to determine the Langmuir parameters, including V L and P L .…”
Section: Pore Characteristicsmentioning
confidence: 99%
“…A description of this method is often found in the literature (Kroos et al 2002;Harpalani et al 2006;Lutyński 2014). The data for calculation was collected from high-accuracy pressure and temperature transducers, connected to a computer and working in continuous mode online.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…The adsorption energy of solid to gas forms the first molecular layer and the adsorption energy of gas to gas forms the second and the rest adsorbed molecular layers. Actually, the BET model can describe the different types of isothermal adsorption curves (Lowell & Shields, 1984;Harpalani, 2006).…”
Section: Classic Adsorption Modelsmentioning
confidence: 99%
“…P 0 is the saturation vapor pressure of the adsorbate at temperature T, and P is the equilibrium vapor (or free gas) pressure (Harpalani, 2006). Dubinin and Radushkevich suggested that the value of n = 2 may be appropriate for some cases, and the equation (D-R equation) can be modified as…”
Section: Classic Adsorption Modelsmentioning
confidence: 99%